2014
DOI: 10.4067/s0718-27242014000300008
|View full text |Cite
|
Sign up to set email alerts
|

How to Justify Purchase of an iPad: Users of the Latest Launch

Abstract: Contemporary technology innovation is increasingly based on convergence and the multiple uses of products. This change is detailed in the literature about new product development, as well as that on systems integration. This article focuses on the factors that determine the justification for using advanced technology products in which the perceived value of the product is not based on its functionality, as much as on its hedonistic or social value as an "all-in-one" product. In this study, consumer behaviors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…However, it is at this point the great trust of Apple as a manufacturer comes in, which may be understood as a level of manufacturer fetishism, but also a well-reasoned faith in Apple's seamless ecosystem, where hardware is supported by tailored operating systems and software, as well as formats for sharing files, movies, music, and the like. In addition, the successful introduction of the iPhone in 2007 may have made the justification for acquiring the first iPad easier [10], by a strengthened enthusiasm among 'Apple believers'. On the one hand, Apple succeeded in mediating this ecosystem to its buyers, by its exclusivity and design approach, and by large-scale launches, fronted by the deceased mythical CEO Steve Jobs.…”
Section: A Technological Ecosystem As a Basis For Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is at this point the great trust of Apple as a manufacturer comes in, which may be understood as a level of manufacturer fetishism, but also a well-reasoned faith in Apple's seamless ecosystem, where hardware is supported by tailored operating systems and software, as well as formats for sharing files, movies, music, and the like. In addition, the successful introduction of the iPhone in 2007 may have made the justification for acquiring the first iPad easier [10], by a strengthened enthusiasm among 'Apple believers'. On the one hand, Apple succeeded in mediating this ecosystem to its buyers, by its exclusivity and design approach, and by large-scale launches, fronted by the deceased mythical CEO Steve Jobs.…”
Section: A Technological Ecosystem As a Basis For Trustmentioning
confidence: 99%
“…With this newer history of the product, our interviews from more than ten years ago were with participants that could have no clue about the coming success, other than confidence in Apple's strategic thinking-ahead. Accordingly, Filho et al, in a study of American iPad first-users, found that the Apple brand provoked such a high level of devotion among consumers that they imagined that the features of the iPad were superior to similar features in other products, even before these were launched on the market [10]. It is evident, however, that the years that have passed have shown us all that the iPad should become an extremely successful innovation that would define a new category of information technological platforms or standards-the 'tablet'.…”
Section: Introductionmentioning
confidence: 99%
“…Ý định thường được định nghĩa là những dấu hiệu cho thấy mọi người sẵn sàng cố gắng như thế nào và dự định sẽ nỗ lực như thế nào để thực hiện hành vi hay chính là trạng thái sẵn sàng để thực hiện một hành vi nhất định và được xem là một tiền đề trước khi thực hiện hành vi 11,16,17 . Hay dự định có ý thức của chủ thể để thực hiện một hành vi nhất định 18,19 . Dehghani và cộng sự 20 cho rằng ý định tiêu dùng là một quá trình quyết định trong đó khách hàng có thể lựa chọn và sử dụng các sản phẩm và dịch vụ.…”
Section: Giả Thuyết Nghiên Cứuunclassified
“…The educational use of tablets with various operating systems (e.g., IOS and Android) has been reported. However, most studies to date have focused on the Apple iPad, due to its widespread popularity and acceptance among students and academics (Nguyen, Barton & Nguyen 2014) and its status as the first multitouch tablet with multi-purpose functionality (Filho, Lima & Lennon, 2014). The portability of tablets has been claimed to encourage flexible learning, as it is not necessary for students to visit ICT labs to use them; tablets can be used anywhere in the school (Brand & Kinash, 2010).…”
Section: Features and Design Characteristics Of Tabletsmentioning
confidence: 99%